Policing child sexual exploitation and abuse cases: a qualitative PRIORITY study of the challenges faced by law enforcement officers in Germany, Portugal, and Sweden - Tselenti, Danai (Policing and society, 2025)
This study aimed to explore the primary challenges experienced by European law enforcement officers who deal daily with child sexual exploitation and abuse (CSEA) investigations. We conducted 6 focus group discussions with 26 criminal investigators and managers from Germany (n = 9), Portugal (n = 9), and Sweden (n = 8). Data were collected as part of the PRIORITY project, whose wider goal is to decrease the occurrence of CSEA by providing anonymous online interventions to individuals concerned about their sexual urges towards children. We employed reflexive thematic analysis at the semantic level. By adopting the Barnahus model as a theoretical lens, we generated three recurring themes and 13 related sub-themes. These overarching themes encompassed a range of organisational barriers, investigative difficulties, and systemic shortcomings and were found to extend across national borders, exhibiting both similarities and context-specific variations across the three countries. We discuss our findings in relation to the most significant policy and practice implications, within the context of the Barnahus model implementation. Additionally, our findings lay the groundwork for five empirically based recommendations aimed at enhancing the effectiveness of future law enforcement responses and prevention efforts in regard to child sexual exploitation and abuse cases at a European level.